Neoadjuvant vascular-targeted photodynamic therapy improves survival and reduces recurrence and progression in a mouse model of urothelial cancer - Barak Rosenzweig (Nature Portfolio, 2021)
Abstract Locally advanced urothelial cancer has high recurrence and progression rates following surgical treatment. This highlights the need to develop neoadjuvant strategies that are both effective and well-tolerated. We hypothesized that neoadjuvant sub-ablative vascular-targeted photodynamic therapy (sbVTP), through its immunotherapeutic mechanism, would improve survival and reduce recurrence and progression in a murine model of urothelial cancer. After urothelial tumor implantation and 17 days before surgical resection, mice received neoadjuvant sbVTP (WST11; Tookad Soluble, Steba Biotech, France). Local and systemic response and survival served as measures of therapeutic efficacy, while immunohistochemistry and flow cytometry elucidated the immunotherapeutic mechanism. Data analysis included two-sided Kaplan–Meier, Mann–Whitney, and Fischer exact tests. Tumor volume was significantly smaller in sbVTP-treated animals than in controls (135 mm3 vs. 1222 mm3, P < 0.0001) on the day of surgery. Systemic progression was significantly lower in sbVTP-treated animals (l7% vs. 30%, P < 0.01). Both median progression-free survival and overall survival were significantly greater among animals that received sbVTP and surgery than among animals that received surgery alone (P < 0.05). Neoadjuvant-treated animals also demonstrated significantly lower local recurrence. Neoadjuvant sbVTP was associated with increased early antigen-presenting cells, and subsequent improvements in long-term memory and increases in effector and active T-cells in the spleen, lungs, and blood. In summary, neoadjuvant sbVTP delayed local and systemic progression, prolonged progression-free and overall survival, and reduced local recurrence, thereby demonstrating therapeutic efficacy through an immune-mediated response. These findings strongly support its evaluation in clinical trials.